Apports nutritionnels, dépense et bilan énergétiques chez l’homme et les primates non-humains : aspects méthodologiques - Laurent Tarnaud; Cécile Garcia; Sabrina Krief; Bruno Simmen (Revue de Primatologie)
This paper presents field methods and laboratory techniques used to evaluate food intake, energy and nutrient input, activity patterns, energy expenditure, and body energy storage in human and non-human primates. The aim is to review both traditional techniques and recent advances in the methods designed to investigate energetic parameters in an anthropobiological perspective. Although most of human habits and behaviours are regarded as culturally determined, Homo as a species share with non-human primates a number of psycho-physiological features originating from biological adaptations and close phylogenetic relationships. Therefore, determining the mechanisms involved in the energetic dynamics in non-human primates may contribute to identify some of these shared biological bases. In this respect, several methods in the field of energetics are applicable to both humans and non-human primates bringing out the similarities of approaches. Besides interspecific comparisons that provide a background to assess the evolution of energy strategies among primates, contrasting the energy fluxes at the population or group level highlights the range of bio-cultural adjustments of humans and non-human primate species to their social and natural environment.The present review distinguishes methods according to the energetic parameters the researcher wishes to describe and quantify: food intake, energy input, energy expenditure associated with behavioural activities, nutritional status and body composition as well as the role of secondary compounds on food items selection and the medicinal properties of plants used. Originally, methods used in the field of energetics were mainly descriptive. Nowadays, they are supplemented with quantitative approaches whose accuracy depends on study populations and field conditions. The behavioral approach for instance is often associated with analyses performed at the laboratory which most often require appropriate facilities and qualified staff. The aim of this review is therefore to enable the researcher to select the appropriate methods for his research objectives and study conditions. The choice of one or several techniques will necessarily reflect a trade-off between accuracy, feasibility and financial cost.